Wear pattern of oil presses - Nekoz, Alexander; Yastreba, Sergey (My University, 2013)
Thus, on the basis of the studies, established features of the microtopography of the surface of the worn parts testify to the different mechanism and type of wear of parts of the inlet and outlet of the presses.
Keywords: mikrotopohrafiyi; surface wear; parts; gear type; press; мікротопографії; поверхні зношення; деталі; механізм; прес; микротопографии; поверхности износа; детали; механизм; тип; пресс